Unveiling Pedagogical Potential: Indonesian Higher Education Students’ Perception on Leveraging BTS’ English Songs for Vocabulary Enhancement - Wahidah, Salma Samrotul; Sri, Melisa; Silvani, Dea (TLEMC (Teaching and Learning English in Multicultural Contexts), 2024)
Song is one of the beneficial learning media to enrich students’ vocabulary mastery and enhance the classroom atmosphere. This qualitative research aims to investigate and describe students’ perceptions of the English song of the idol group ‘BTS’, which are used as a learning medium to learn English, especially for vocabulary mastery. This research focuses on students who are the BTS fans as research targets. This research aims to gain an in-depth understanding of the experiences, perceptions, or opinions of seven students aged between 17 to 22 years old. The data were obtained through semi-structured interview, and the data were analyzed by thematic analysis. The research results show that all the students have positive perceptions towards using BTS’ English songs as a learning medium in learning English Vocabulary. The songs succeeded in constructing students’ interest to learn English. In addition, the songs were able to facilitate students in improving vocabulary mastery, pronunciation, and understanding of the meaning and idiom or slang. Keywords: English song, vocabulary enhancement, BTS